Combined systemic inflammatory immunity index and prognostic nutritional index scores as a screening marker for sarcopenia in patients with locally advanced gastric cancer - Ding, Ping'an; Lv, Jingxia; Sun, Chenyu; Chen, Shuya; Yang, Peigang; Tian, Yuan; Zhou, Qin; Guo, Honghai; Liu, Yang; Zhao, Qun (Frontiers in Nutrition, 2022)
Background: Sarcopenia is associated with poor clinical outcomes in patients with locally advanced gastric cancer (LAGC). Currently, the diagnostic criteria for sarcopenia are complex and laborious. Increased evidence suggests the inflammatory state of the body is closely associated with the development of sarcopenia. The systemic immune-inflammatory index (SII) and the prognostic nutritional index (PNI) are representative blood indicators of the status of the systemic inflammatory response, but the clinical significance of the combined testing of these two indicators remains unclear. We aimed to develop a simple and practical risk score (SII-PNI score) to screen patients with LAGC for sarcopenia on admission for early diagnosis. Methods: We registered a prospective clinical study (NCT01516944) from January 2011 to March 2016 involving 134 patients with LAGC undergoing radical surgical resection. All patients followed the definition of sarcopenia in the Asian Sarcopenia Working Group (ASWG) guidelines and were divided into sarcopenia and non-sarcopenia groups. SII-PNI score 0~2 was scored as 2 for high SII (≥432.9) and low PNI (≤49.5); score 1, either high SII or low PNI; score 0, no high SII or low PNI. Results: All patients underwent radical surgery, including 31 patients (23.13%) with sarcopenia according to AGWS criteria. The SII-PNI score was significantly lower in the non sarcopenic patients than in the sarcopenic patients (p=0.041). Logistic multivariate analysis showed that the SII-PNI score predicted an independent prognostic factor for sarcopenia (p<0.001). Patients with high SII-PNI scores had significantly worse prognosis than those with low SII-PNI scores (p<0.001). The SII-PNI score was an independent prognostic factor for predicting overall survival and disease-free survival survival (p=0.016, 0.023). Conclusion: Peripheral blood parameters SII-PNI scores accurately identify sarcopenia in patients with LA-GC and could be used as potential systemic markers.